Social preferences under uncertainty - Alexia Gaudeul (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Willingness to take risk depends on whether the risk affects others as well as oneself and on how the risk affects ones position vis-á-vis others. Taking a bet can improve ones position relative to others or threaten it. We present an experiment that explores individual attitudes to lotteries that involve both oneself and another subject. Individuals consistently and strongly dislike obtaining safe but unfair social outcomes rather than playing fair but risky social lotteries. This effect is apparent whether the unfair safe social outcome benefits them or the other. Subjects are also more risk averse when facing social lotteries than when facing lotteries that involve only themselves. There is a small but consistent and significant tendency to avoid social lotteries that impose a risk on the other. An attempt to reconcile those findings with standard models of social preferences shows that a high weight given to considerations of ex-ante inequality goes some way towards explaining the decisions of our subjects. It remains difficult however to account for the magnitude of their aversion to safe but unequal social outcomes.
Keywords: C91; D63; D81; 330; altruism; inequality aversion; procedural fairness; risk attitudes; social preferences; utility measurement